MEDIA PEMBELAJARAN INTERAKTIF PENGENALAN ILMU TAJWID BERBASIS AUGMENTED REALITY - Jalaludin Assuyuthi, Muhammad; Ekawati, Nia (JURNAL ILMIAH INFORMATIKA, 2024)
Mastery of tajweed is an important aspect in reading the Qur'an correctly, but often conventional learning methods are considered less attractive to students. To overcome this challenge, this research developed an interactive learning media based on Augmented Reality (AR) that is designed to introduce the science of tajweed in a more interesting and easy-to-understand way. Augmented reality (AR) technology allows for the integration of digital elements into the real world, creating immersive and interactive learning experiences. This application provides a three-dimensional visualization of the hijaiyah letters and the rules of tajwid, as well as examples of their application in the reading of the Qur'an. The evaluation of the use of this media shows an increase in students' interest and understanding of tajweed materials, as well as providing a more in-depth and interesting learning experience. Thus, this AR-based interactive learning media has the potential to be an effective tool in the process of introducing and mastering tajweed science, which is expected to improve the quality of learning in the religious field.